The Effect of titanium dioxide nanoparticles on the activity of salivary peroxidase in periodontitis patients - Talib, Mays A; Ali, Basima G; Al-Rubaee, Eaman A; Mahdy, Maysaa (Journal of Baghdad College of Dentistry, 2023)
Background:The technology of nanoparticles has been expanded to many aspects of modern life. Titanium dioxide nanoparticles were of many nanomaterials utilized in biomedical applications. The interactions between nanoparticles and proteins are believed to be the base for the biological effect of the nanoparticles. The oxidation reaction of many substances is catalyzed by oxidizing enzymes called peroxidases. The activity of salivary peroxidase is elevated with periodontal diseases. the aim ofthis study is to examine the action of titanium dioxide nanoparticles on salivary peroxidase activity.Material and method75 participants were enrolled in this study—Periodontitis group with 44 participants and the non-periodontitis group with 31 participants. The participants' age range was 35 to 50 years for both groups. The clinical parameters of plaque index, gingival index, probing pocket depth and clinical attachment level were used in this study to determine the presence or absence of the periodontal disease. Unstimulated saliva was collected from all participants and analyzed for the activity of peroxidase enzyme under the effect of titanium dioxide nanoparticles. ResultsThe Periodontitis group showed higher peroxidase enzyme activity than the non-periodontitis group and the activity of salivary peroxidase showed no correlation with the clinical parameters. Titanium dioxide nanoparticles increased salivary peroxidase activity. ConclusionThis study demonstrated that the solid surface of nanoparticles could induce changes in the attached protein molecule which in turn causes changes in the effect of the nanoparticles on living tissue or organism. The titanium dioxide nanoparticles Play a role in increasing the activity of salivary peroxidase within the saliva of chronic periodontitis patients.